GREEN BRAND: AN INTEGRATED CONCEPTUAL FRAMEWORK - Mihai STOICA (Management & Marketing)
The increase in the number of consumers who choose to focus on sustainable consumption has led companies to develop a series of solutions to match their needs and desires. Developing a brand that integrates the green philosophy of the organization can result in a heightened attachment to the brand from receptive consumers to the ecological principles. In this context, the concept of green brand has begun to attract the attention of many brand management practitioners and academics. However, at the organizational level, the decision to associate a series of green values with a brand is not a sufficient measure to classify the brand as a green brand. For this reason, it is necessary to define the concept of green brand, starting from the opinions expressed by the specialists in the field. Therefore, this paper follows an exploratory approach in terms of defining the green brand and highlighting its specific features. Additionally, the dimensions of brand equity will be customized for a green brand. At the practical level, companies have the possibility to create a new green brand or they can resort to a brand extension. These alternatives are presented in the paper.